Quantum-chemical modeling in assessing the interaction of diesel fractions hydrocarbons with a depressant and depressant-dispersant additive; Химия и химическая технология в XXI веке; Т. 2 - Berdnikova A. A. (Химия и химическая технология на иностранном языке (английский), 2021)
Заглавие с титульного экрана